Advances in paediatric pulmonary vascular disease associated with bronchopulmonary dysplasia. (February 2014) - Rossor, Thomas; Greenough, Anne
<x xml:space="preserve">Abstract</x> Pulmonary hypertension (PH) is a common finding in infants with bronchopulmonary dysplasia (BPD). The aim of this review is to describe recent advances in the diagnosis and treatment of PH and discuss whether they will benefit infants and children with BPD related PH. Echocardiography remains the mainstay of diagnosis but has limitations, further developments in diagnostic techniques and identification of biomarkers are required. There are many potential therapies for PH associated with BPD. Inhaled nitric oxide has been shown to improve short term outcomes only. Sidenafil in resource limited settings was shown in three randomized trials to significantly reduce mortality. The efficacy of other therapies including prostacyclin, PDE3 inhibitors and endothelin receptor blockers has only been reported in case reports or case series. Randomized controlled trials with long term follow up are required to appropriately assess the efficacy of therapies aimed at improving the outcome of children with PH.